The Development of Assessment Instruments with Problem Posing Methods to Measure Students Creative Thinking Ability in Acid Base Materials - Pitri Rahma Dewi; Maria Erna; Rasmiwetti Rasmiwetti (Universitas Riau, 2020)
Students creative thinking skills play an important role in achieving educational goals, especially in understanding chemical material. Education is currently focused on developing Higher Order Thinking Skills and creative thinking skills that are one of the highest level of thinking. The teacher as one of the creative drivers is an important factor to increase student creativity in school. This study aims to develop creative thinking assessment instruments with problem posing methods on acid-base material and conduct tests to determine the responses of educators and students. This research used the Research and Development method which refers to the Borg and Gall model. The sample in this study amounted to 60 class XI high school students in Rokan Hulu district. The results of the validation of the assessment instruments were in average of more than 0.78 (very good) and had a test reliability on the main field test of 0.88 which was classified as very high. The level of difficulty ranged from 0.29 - 0.56 with the category of difficult and moderate. The ability to differentiate the problem is good enough. And the results of student responses amounted to 50.4 on the questionability readiness questionnaire, 8.1 on the questionnaire for sufficient time. Whereas the result of the teacher's response was 57.3 on the question eligibility questionnaire.